Expression of Cytosolic Phospholipase A2α in Murine C12 Cells, a Variant of L929 Cells, Induces Arachidonic Acid Release in Response to Phorbol Myristate Acetate and Ca2+ Ionophores, but Not to Tumor Necrosis Factor-α - Masaya Shimizu; Chihiro Azuma; Tomoko Taniguchi; Toshihiko Murayama (Elsevier, 2004)
Tumor necrosis factor-α (TNFα)-induced cell death is regulated through the release of arachidonic acid (AA) by group IVA cytosolic phospholipase A2 (cPLA2α) in the murine fibroblast cell line L929. However, the signaling pathway by which TNFα activates cPLA2α remained to be solved. We examined AA release in L929 cells, in a variant of L929 (C12 cells) lacking cPLA2α, and in C12 cells transfected with cPLA2α expression vectors. In transient and stable clones of C12 cells expressing cPLA2α, Ca2+ ionophore A23187 and phorbol myristate acetate (PMA) stimulated AA release within 90 min, although no response to TNFα was observed within 6 h. These results suggest that C12 cells may lack the components necessary for TNFα-induced AA release, in addition to cPLA2α. PMA is known to stimulate AA release via phosphorylation of Ser505 in cPLA2α by activating extracellular signal-regulated kinases (ERK1/2). However, PMA-induced AA release from C12 cells expressing mutant cPLA2αS505A (mutation of Ser505 to Ala), which is not phosphorylated by ERK1/2, was similar to that from L929 cells and C12 cells expressing wild-type cPLA2α. The role of Ser505 phosphorylation in AA release induced by PMA is also discussed. Keywords:: cytosolic phospholipase A2α, tumor necrosis factor, Ca2+ ionophore, phorbol myristate acetate, L929 and C12 cells